The Old Dark House and the Space of Attraction - Spadoni, Robert (Cinémas, 2010)
Writers have invoked the concept of the “cinema of attractions,” from early cinema studies, to claim that horror films sacrifice narrative integrity to deliver sudden frights and spectacular shocks. An examination of the history of the concept of the attraction, however, finds it heavily theorized by Sergei Eisenstein as something that can bind films together in powerful ways. In one horror film, The Old Dark House (1932), slamming doors, quaking thunder, shattering glass and a rampaging mute butler, while scary, also figure in James Whale’s scheme to criss-cross his film with motifs and other repetitions and produce a work that gains with every viewing. Even with its thin narrative, stock characters and, already in 1932, very familiar story about characters trapped in an old dark house, the film hangs together in intricate ways. Most elaborately, Whale embeds attractions in a grid that overlays the tiered spaces of the setting. Characters move up and down the creaky staircases and along the suspended hallways, chasing each other, scuffling, and withholding and disclosing secrets. Scenographic and narrative space mesh into a tight unity lit up by a constellation of “fun house” jolts. Props, including lamps and knives, circulate through these spaces as well, tracing patterns that startle viewers while simultaneously rendering the film rigorously and beautifully coherent.